Van niemandsland tot de ‘grote klaprozenexplosie’. Twee decennia onderzoek over België in de Eerste Wereldoorlog, 1995-2014 - Vrints, Antoon (BMGN - Low Countries Historical Review, 2016)
From No-Man’s Land to the ‘Great Poppy Explosion’: Two Decades of Research into Belgium in the First World War, 1995-2014 During the last twenty years the historiography on Belgium during the First World War has been undergoing a true transformation. Originally a neglected topic, it became the focus of an established sub-discipline. The Belgian case was finally integrated in the vital international research landscape on the First World War. Purpose of this article is to make a (preliminary) overview of these developments by identifying the major conceptual and thematic evolutions. The question is addressed how the historiography of Belgium during the First World War could develop from a marginal to a respectable field. Following aspects of war history are discussed: the position of the German invaders and occupiers, the Belgian front experience, the Belgian civilian experiences in the occupied country and in exile and settling / memory of the war. De historiografie over België tijdens de Eerste Wereldoorlog heeft de afgelopen twintig jaar een ware transformatie doorgemaakt. Van een verwaarloosd onderwerp werd het de inzet van een gevestigde subdiscipline. Aansluiting werd bovendien gevonden bij het vitale internationale onderzoekslandschap over de Eerste Wereldoorlog. Oogmerk van dit artikel is een (voorlopig) bilan van die ontwikkelingen op te maken door de belangrijkste conceptuele en thematische evoluties te duiden. Geanalyseerd wordt hoe de historiografie over België zich tijdens de Eerste Wereldoorlog van een marginaal tot een respectabel veld kon ontwikkelen. Daarbij worden de volgende facetten van de oorlogsgeschiedenis behandeld: de positie van de Duitse invallers en bezetters, de Belgische frontervaring, de Belgische civiele ervaringen in het bezette land en in ballingschap en de afwikkeling van/herinnering aan de oorlog.